Solve for y.

2x + y = 1

y = 1 - 2x (subtract 2x)

Substitute for x

y = 1 - 2{-2, 1, 4) = 1 + {4, -2, -8} =

Answer (C) seems to match.

_____

You can do the substitution one number at a time, but sometimes it is convenient just to do them all at once.

2x + y = 1

y = 1 - 2x (subtract 2x)

Substitute for x

y = 1 - 2{-2, 1, 4) = 1 + {4, -2, -8} =

**{5, -1, -7}**Answer (C) seems to match.

_____

You can do the substitution one number at a time, but sometimes it is convenient just to do them all at once.